The use of virtual reality in rehabilitation of postural changes in young adults (Research, Society and Development, 2020)
Introduction: Over time, individuals suffer direct interference stumuities in their posture, leading to imbalance and disharmony in osteomyoarticular synergism, bringing negative consequences about the ideal postural alignment. Objective: to verify the effect of virtual reality on the rehabilitation of postural deviations in sedentary male individuals. Methods: This is a near-experimental and quantitative study composed of 10 sedentary male individuals, aged between 18 and 40 years. In which, initially, sociodemographic and clinical data were collected; subsequently performed an evaluation, in the anterior, posterior and lateral views through the postural evaluation form. The intervention consisted of 5 10-minute sessions on the Nintendo console®, for feedback the balance board and the Wii Fit program ®. Results: No differences were found in any postural point evaluated. Conclusion: In the present study there were no trends of improvement in the correction of postural changes, showing no corrective effects on postural deviations of the individuals evaluated.